Real-world practice of conversion surgery for unresectable hepatocellular carcinoma - a single center data of 26 consecutive patients - Bo Zhang; Xuetao Shi; Kai Cui; Zhongchao Li; Lei Li; Zhaogang Liu; Chengsheng Zhang; Pengfei Sun; Jingtao Zhong; Zhicheng Sun; Zhibin Chang; Zhao Ma; et al. (BMC Cancer, 2023)
Abstract Aim To understand the proportion of uHCC (unresectable hepatocellular carcinoma) patients who achieve successful conversion resection in a high-volume setting with state of the art treatment options. Methods We retrospectively reviewed all HCC patients hospitalized to our center from June 1st, 2019 to June 1st, 2022. Conversion rate, clinicopathological features, response to systemic and/or loco-regional therapy and surgical outcomes were analyzed. Results A total of 1,904 HCC patients were identified, with 1672 patients receiving anti-HCC treatment. 328 patients were considered up-front resectable. Of the remaining 1344 uHCC patients, 311 received loco-regional treatment, 224 received systemic treatment, and the remainder (809) received combination systemic plus loco-regional treatment. Following treatment, one patient from the systemic group and 25 patients from the combination group were considered to have resectable disease. A high objective response rate (ORR) was observed in these converted patients (42.3% under RECIST v1.1 and 76.9% under mRECIST criteria). The disease control rate (DCR) reached 100%. 23 patients underwent curative hepatectomy. Major post-operative morbidity was equivalent in the both groups (P=0.76). Pathologic complete response (pCR) was 39.1%. During conversion treatment, grade 3 or higher treatment-related adverse events (TRAEs) were observed in 50% of patients. The median follow-up time was 12.9 months (range, 3.9~40.6) from index diagnosis and 11.4 months (range, 0.9~26.9) from resection. Three patients experienced disease recurrence following conversion surgery. Conclusions By intensive treatment, a small sub-group of uHCC patients (2%) may potentially be converted to curative resection. Loco-regional combined with systemic modality was relative safe and effective in the conversion therapy. Short-term outcomes are encouraging, but long-term follow-up in a larger patient population are required to fully understand the utility of this approach.